Surface Electromyography Meets Biomechanics: Correct Interpretation of sEMG-Signals in Neuro-Rehabilitation Needs Biomechanical Input - Disselhorst-Klug, Catherine; Williams, Sybele (Frontiers in Neurology, 2020)
Coordinated activation of muscles is the basis for human locomotion. Impaired mus-cular activation is related to poor movement performance and disability. To restore movement performance, information about the subject’s individual muscular activa-tion is of high relevance. Surface electromyography (sEMG) allows the pain-free assessment of muscular activation and many ready-to-use technologies are availa-ble. They enable the usage of sEMG measurements in several applications. Howev-er, due to the fact that in most rehabilitation applications dynamic conditions are an-alysed, the correct interpretation of sEMG signals remains difficult which hinders the spread of sEMG in clinical applications. From biomechanics it is well known that the sEMG signal depends on muscle fiber length, contraction velocity, contraction type and on the muscle’s biomechanical moment. In non-isometric conditions these bio-mechanical factors have to be considered when analysing sEMG signals. Addition-ally, the central nervous system control strategies used to activate synergistic and antagonistic muscles have to be taken into consideration. These central nervous system activation strategies are rarely known in physiology and are hard to manage in pathology. In this perspective report we discuss how the consideration of biomechanical factors leads to more reliable information extraction from sEMG signals and how the limita-tions of sEMG can be overcome in dynamic conditions. This is a prerequisite if the use of sEMG in rehabilitation applications is to extend. Examples will be given showing how the integration of biomechanical knowledge into the interpretation of sEMG helps to identify the central nervous system activation strategies involved and leads to relevant clinical information.